Adobe Premiere Pro CC - Jago, Maxim (Classroom in a book., 2015)
The fastest, easiest, most comprehensive way to learn Adobe Premiere Pro CC (2014 release) Classroom in a Book®, the best-selling series of hands-on software training workbooks, offers what no other book or training program does--an official training series from Adobe Systems Incorporated, developed with the support of Adobe product experts. Adobe Premiere Pro CC Classroom in a Book contains 19 lessons that cover the basics, providing countless tips and techniques to help you become more productive with the program. You can follow the book from start to finish or choose only those lessons that interest you. In addition to learning the key elements of the Adobe Premiere Pro interface, this completely revised CC (2014 release) edition covers new features, including "scratch" track recording, Master Clip effects, and masking and tracking visual effects. Access to all of the project files used in the book's lessons are included with purchase of the book. Print editions come bundled with a DVD containing the lesson files, and students who purchase an eBook edition receive a code that lets them download the lesson files from their account page on peachpit.com. Both print and eBook users also get access to downloadable updates that cover new features that Adobe releases for Creative Cloud members. "The Classroom in a Book series is by far the best training material on the market. Everything you need to master the software is included: clear explanations of each lesson, step-by-step instructions, and the project files for the students." Barbara Binder, Adobe Certified Instructor Rocky Mountain Training